2009
DOI: 10.1007/s00520-009-0719-y
|View full text |Cite
|
Sign up to set email alerts
|

To foster healing among adolescents and young adults with cancer: What helps? What hurts?

Abstract: How people communicate information, tasks, and feelings to AYA patients and survivors affects how they experience their illness and think about themselves and their current and future situations. All parties-doctors, other medical providers, family members, and friends-need to attend to the manner as well as content of their communications and interactions with AYAs and to the social and emotional context within which communication and interaction occurs. Specific recommendations for the care of AYA cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 9 publications
7
104
0
Order By: Relevance
“…Production of this report has been made possible through a financial contribution from Health Canada through the Canadian Partnership Against Cancer, and through the support of the C 17 Council, the national network of Canadian pediatric hematology/oncology programs. The Canadian Partnership Against Cancer is an independent organization funded by the federal government to accelerate action on cancer control for all Canadians.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of this report has been made possible through a financial contribution from Health Canada through the Canadian Partnership Against Cancer, and through the support of the C 17 Council, the national network of Canadian pediatric hematology/oncology programs. The Canadian Partnership Against Cancer is an independent organization funded by the federal government to accelerate action on cancer control for all Canadians.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The diagnosis and treatment of cancer in this age group may have a significant impact on quality of life, productivity, social and family relationships, cognitive functioning, and other aspects of development long after treatment completion. 1,4,5,17 Developmental tasks of young adulthoodincluding establishing meaningful relationships, completing higher education, becoming financially independent, and developing an autonomous identity-can be disrupted or delayed. AYA patients experience distress, anxiety, and depression, and require psychosocial and supportive care expertise.…”
Section: Psychosocial Needsmentioning
confidence: 99%
“…Research over the last 20 years has indicated that AYAs with cancer are a forgotten population who require closer study in order to understand their unique problems [1][2][3][4][5][6][7][8][9] prompting Michelagnoli, Pritchard and Phillip [3] to describe this group of people as a lost tribe. One factor identified to account for this disadvantage is the fragmentation of services [1,[10][11][12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…hematopoietic stem cell transplantation) [125], have the potential to influence adherence. Peer support and dedicated support groups may help deal with some of these psychosocial barriers in AYAs with cancer [112,125]. A comprehensive care framework, addressing linguistic, cultural, social and other issues, results in high adherence in certain populations, such as children and adolescents with SCD [78].…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%
“…This technology base may enable effective, standardized and cost-effective assessment of adherence and intervention [110], especially in AYAs who are highly engaged in media-based social networking and seeking health information [111]. Web-based interventions can disperse educational material and facilitate tailored health promotion, peer support [112] and attendance of clinic appointments, as shown, for example, in AYA cancer survivors [113] and AYAs with SCD [26,50]. …”
Section: Adolescents and Young Adultsmentioning
confidence: 99%